Euro Dinar Trading Analysis Using WARIMA Hybrid Model - Wazeer, Elaf Alaa Al-deen; Hameed, Lamyaa Mohammed Ali (Journal of Economics and Administrative Sciences, 2022)
The rise in the general level of prices in Iraq makes the local commodity less able to compete with other commodities, which leads to an increase in the amount of imports and a decrease in the amount of exports, since it raises demand for foreign currencies while decreasing demand for the local currency, which leads to a decrease in the exchange rate of the local currency in exchange for an increase in the exchange rate of currencies. This is one of the most important factors affecting the determination of the exchange rate and its fluctuations. This research deals with the currency of the European Euro and its impact against the Iraqi dinar. To make an accurate prediction for any process, modern methods can be used through which the model is developed. One of the most important modern methods that smooth the time series and purify it from noise is the wavelet transformation and in order to predict time series data using a new technique that combines the classic ARIMA method and the technique of Wavelet transformation, and this is called Wavelet-ARIMA hybrid model, as it was applied to data for a weekly time series of the rate of change in prices, buying and selling the European euro currency against the Iraqi dinar on the classic ARIMA model and the hybrid Wavelet-ARIMA model. The comparison was made between ARIMA and Wavelet-ARIMA models using several functions, including Haar, Db4 and Db6 to forecast the model that achieves better results for 64 weeks. As the hybrid model with Db6 function achieves better results, as the euro currency continues to increase, this negatively affects the Iraqi citizen in terms of high prices and positively on the country’s economy